SEXUAL BEHAVIOR ASSOCIATED WITH THE RISK OF ABNORMAL PAP TEST - Antić, Ljiljana (PONS - medicinski časopis, 2017)
ABSTRACT Serbia has the highest incidence of cervical cancer among the countries of South East Europe. AIM: Determine risk factors for the incidence of cervical cancer in women in Serbia and testing their association with an abnormal Pap test. METHOD: The study of risk sexual behaviors of developing cervical cancer, carried out by the type of cross-sectional studies. The studied population is between 525 patients, aged 18 to 69 years. RESULTS: We have identified three risk factors for an abnormal Pap test: early sexual activity, greater number of sexual partners and STDs in history. CONCLUSION: The results indicate the need for inclusion of selected family doctors and nurses and midwives in the Visiting Nurse Service of health, to recognition the population of women at increased risk of developing cervical cancer. Keywords: cervical cancer, Pap test, sexual behaviors, contraception